Comparing nursing handover and documentation: forming one set of patient information. (6th December 2013) - Johnson, M.; Sanchez, P.; Suominen, H.; Basilakis, J.; Dawson, L.; Kelly, B.; Hanlen, L.
<x xml:space="preserve">Abstract</x> Aim The aim of this study was to explore the potential for one set of patient information for nursing handover and documentation. Background Communication of patient information requires two processes in nursing: a verbal summary of the patients' care and another report within the nursing notes, creating duplication. Introduction Advances in speech recognition technology have provided an opportunity to consider the practicality of one set of information at the nursing end‐of‐shift. Methods We used content analysis to compare transcripts from 162 digitally recorded handovers and written nursing notes for similar patients within general medical‐surgical wards from two metropolitan hospitals in Sydney Australia. Findings Using the Nursing Handover Minimum Dataset analysis framework similar content [n = 2109 (handover) n = 1902 (nursing notes)] was found within the handovers and notes at the end‐of‐shift (7:00 am and 2:00 pm). Analysis of the overarching categories demonstrated the emphasis within the differing data sources as: patient identification (31%), care planning or interventions (25%), clinical history (13%), and clinical status (13%) for handover, vs. care planning (47%), clinical status (24%), and outcomes or goals of care (12%) for nursing notes. Discussion This study has demonstrated that similar patient information is presented at handover and within documentation. Major categories are consistent with international nursing minimum datasets in use. Conclusion We can use one set of patient information (within some limitations) for two purposes with system design, practice change and education. Experiments are currently being conducted trialling speech recognition within laboratory and clinical settings. Implications for Nursing and Health Policy One set of patient information, verbally generated at handover delivering electronic documentation within one process, will transform international nursing policy for nursing handover and documentation.